Optimization of enrichment and isolation media of thermophilic hydrocarbonoclastic bacteria isolated from oil reservoir of West Java for microbial enhanced oil recovery (MEOR) application - Astuti, Dea Indriani; Purwasena, Isty Adhitya; Satrio, Gregorius Gilang; Andika, Kelvin Rachmad; Millati, Ghaida Zainiya; Dwiningrum, Tera Wahyu; Meriani, Evita (Penerbit Universiti Kebangsaan Malaysia, 2020)
Microbial enhanced oil recovery (MEOR) is a tertiary oil recovery process which aims to increase the crude oil recovery uptake to 55% from its original oil in place. In its application, indigenous microorganisms are commonly used as the main biological agents, but the isolation processes become more complicated due to environment’s extreme condition. This study aims to determine the optimum formulation for the enrichment and isolation medium, in order to obtain a highly diverse of indigenous hydrocarbonoclastic bacteria. The isolation process was carried out in two stages; the isolation of mild oil fraction degrading bacteria, and isolation of the heavy oil fraction degrading bacteria which confirmed by the SARA (saturated, aromatic, resinic, and asphaltic) fraction chromatography analysis. Four enrichment and five isolation media were formulated based on the distinction in the macro-and micronutrient composition. Overall, a total of 92 isolates were successfully isolated. The highest bacterial diversities were achieved in the enrichment medium B (crude oil used as carbon source which supplemented with sodium lactate) and isolation medium I (nutrient agar with twice agar concentration), each with 37 and 33% of obtained isolates, respectively. The newly formulated medium can be further utilized to isolate various types of indigenous bacteria from the oil well which were able to degrade SARA fraction from crude oil. The result showed that ABG2-7 as the isolate with the highest activity on SARA degradation. The amount of 15% inoculum of ABG2-7 isolate was able to degrade heavy crude oil, thus might serve as potential bacteria for MEOR application.